2022
DOI: 10.25236/ijfm.2022.040306
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress in Relationship between Chronic Inflammation and Development of Esophageal Cancer

Abstract: As a common malignant tumor of the digestive tract, esophageal cancer has a high incidence in China, accounting for about half of the global incidence. The pathogenic factors are complicated, primarily related to eating diet, obesity, gastroesophageal reflux disease, and Barrett's esophagus. In this article, through the literature search of Web of Science, PubMed, and CNKI, we analyzed the transformation of inflammatory cells cytokines. We activated the inflammatory pathway in chronic inflammation of the esoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…However, other extrinsic factors likely also play a role in the progression process. Together with genomic alterations, there is accumulating evidence that the inflammatory microenvironment (iME) plays a role in the progression process by contributing to inhibiting apoptosis, enabling immune evasion, and promoting proliferation, angiogenesis, invasion, and metastasis [13,14]. Studies in the microenvironment of BE have revealed the involvement of lymphoid cells (i.e., T cells, B cells, and NK cells) and myeloid-derived cells (i.e., macrophages, neutrophils, eosinophils), as well as their secreted cytokines and chemokines [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…However, other extrinsic factors likely also play a role in the progression process. Together with genomic alterations, there is accumulating evidence that the inflammatory microenvironment (iME) plays a role in the progression process by contributing to inhibiting apoptosis, enabling immune evasion, and promoting proliferation, angiogenesis, invasion, and metastasis [13,14]. Studies in the microenvironment of BE have revealed the involvement of lymphoid cells (i.e., T cells, B cells, and NK cells) and myeloid-derived cells (i.e., macrophages, neutrophils, eosinophils), as well as their secreted cytokines and chemokines [15,16].…”
Section: Introductionmentioning
confidence: 99%